Profit or politics? Understanding renationalizations in Russia - Chernykh, Lucy (Journal of Corporate Finance, 2011)
This study examines firm-level determinants of the government incentives to acquire controlling stakes in private companies. Using a novel hand-collected dataset of 153 largest listed and unlisted Russian companies, I investigate the methods and the rationales of a 2004–2008 wave of selected nationalizations in a post-privatization market. I find robust evidence that formerly privatized and domestically-owned companies in strategically important sectors face the highest risks of corporate control transfers from private to state hands. I also find that the corporate tax evasion is another significant determinant of a firm nationalization. Contrary to commonly held beliefs, there is little evidence that renationalizations in Russia are driven by firm profitability factors: the government neither systematically “cherry-picks” best performers nor addresses market failures by rescuing national champions in financial distress. These results contribute to t'he politics and finance literature by providing new firm-level evidence on the importance of strategic nationalism in the government's decision to intervene into the corporate control structures.